Disaster And its Threat To Food: Analysis Of Crisis Management On Meat Products And Seafood Towards Food Traceability In Malaysia - Alina Abdul Rahim; Norhayati Rafida Abdul Rahim; Mariam Abdul Latif; Noorhasifah Abdul Aziz; Zaiton Hasan; Mohd Sukri Hassan (Universiti Sains Islam Malaysia, 2024)
Disaster And its Threat To Food: Analysis Of Crisis This study aims to assess and evaluate the disaster response system of food in Malaysia, the capacity to respond to disasters, and to promote the strategy for the dissemination of disaster management. The effectiveness of an emergency response in Malaysia will depend on the national food safety system in place and public health preparedness planning for emergency situations and preparedness plans that are developed and implemented long before any event occurs. For disaster which is classified as non-disastrous, the relevant agencies can handle using minimum resources and facilities at local level. In case of disaster caused by fire or hazardous materialsp (hazmat), Fire and Rescue Department Malaysia will act as a main agency to handle it. District Police Chief or State Police Chief which is relevant, still hold the responsibility as commander of disaster operation on scene to coordinate the involvement of the other agencies. Among the non-disastrous incidents are the vehicle accidentqthe small fire or a mishap in a lake or river. Therefore going by this directive, Emergency Rensponse Team (ERT) has a role to contribute and play in both disastrous and non disastrous disaster in assisting the government machinery.